PERBAIKAN INTERFERENSI GELOMBANG RF ANTARA VHF APP DAN VHF ER MENGGUNAKAN CAVITY FILTER (STUDI KASUS BANDARA SULTAN SYARIF KASIM II PEKAN BARU) - Mutiara Widasari Sitopu; Catra Indra Cahyadi (Jurnal Penelitian)
This study describes the improvement of radio frequency VHF APP and VHF ER caused by bandwidth widening. VHF is the frequency used to transmit data that is transmitted in all directions. VHF A/G is an equipment used for communication between air traffic control (ATC) and pilot with a frequrncy range of 117.9 MHz – 137 MHz. To overcome the widening of the bandwidth, re-setting is done by using a cavity filter with a resonant frequency of 132.3 MHz and passing frequencies above the cut-off frequency. With the re –setting using a cavity filter, the bandwidth can be narrowed again so as to eliminate interference between VHF APP radios and VHF ER, but as a result the transmit power distance on VHF is reduced but does not reduce the performance of the radio. Keywords: interference; cavity filter